First records of the seven‐gilled Notorynchus cepedianus and six‐gilled Hexanchus griseus sharks (Chondrichthyes: Hexanchiformes: Hexanchidae) found in the Galápagos Marine Reserve. Issue 3 (30th July 2020) - Buglass, Salome; Nagy, Shannon; Ebert, David; Sepa, Paulina; Turchik, Alan; Bell, Katherine L. C.; Rivera, Fernando; Giddens, Jonatha
Abstract: This study reports the first records of cowsharks (Hexanchidae) in the Galápagos Islands, in particular Notorynchus cepedianus and Hexanchus griseus, observed between depths of 210 and 418 m on footage from free‐falling autonomous deep‐ocean cameras. These sightings provide new information on the habitat preferences and range distribution for N. cepedianus and the first records of H. griseus in Ecuadorian waters. The findings support the formulation of regional conservation strategies for these large apex predator species and highlight the limited biological knowledge of Galápagos' deep‐water ecosystems.